2011
DOI: 10.2478/v10220-011-0012-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Housing System on Egg Quality in Laying Hens

Abstract: the aim of the study was to evaluate the quality of eggs from hybrids of laying hens of selected Polish breeding strains depending on their housing system. analysis was made of eggs from Ka-62, Ka-42, Ka-68 and Ka-48 hybrids housed in three systems: cage, litter and free range. one hundred eggs, randomly chosen from each experimental group between 34 and 36 weeks of age, were evaluated for a set of physical characteristics such as weight of egg and egg fraction, percentage of main egg fractions, egg shape inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 6 publications
7
26
0
1
Order By: Relevance
“…In cages, the egg weight was increased with age within 1 g, whereas in free range, the weight increased to almost 9 g. These results are in correspondence with Van Den Brand et al (2004), who also detected an interaction of age and the housing system, and the free range layers had eggs with lower weight than the cage layers at the beginning of the experiment; however, the egg weight in eggs from free range increased faster after 59 weeks and was greater than the egg weight Lewko and Gornowicz (2011), who also found heavier eggs in cages in comparison with free range. However, Hidalgo et al (2008) reported that free range layers produced heavier eggs compared to other systems.…”
Section: Discussionsupporting
confidence: 80%
“…In cages, the egg weight was increased with age within 1 g, whereas in free range, the weight increased to almost 9 g. These results are in correspondence with Van Den Brand et al (2004), who also detected an interaction of age and the housing system, and the free range layers had eggs with lower weight than the cage layers at the beginning of the experiment; however, the egg weight in eggs from free range increased faster after 59 weeks and was greater than the egg weight Lewko and Gornowicz (2011), who also found heavier eggs in cages in comparison with free range. However, Hidalgo et al (2008) reported that free range layers produced heavier eggs compared to other systems.…”
Section: Discussionsupporting
confidence: 80%
“…Only shell thickness and dirty egg differed significantly (P<0.01) between two housing systems, but other quality parameters were similar between two housing systems (Table 3). Present study and some other observations (Lewko and Gornowicz, 2011;Dukic-Stojcic et al, 2009) found no significant difference on shape index between barn and cage eggs. However, Mohan et al (1991) found significantly higher shape index in barn than in cage.…”
Section: Resultsmentioning
confidence: 50%
“…However, there were also other (Singh et al, 2009;Lewko and Gornowicz, 2011) reports that more yellowish yolk color in eggs from barn. In addition, housing system did not affect any significant difference on yolk index (Table 4) Where, higher score represents more yellowish yolk ( 접수: 2013.…”
Section: Resultsmentioning
confidence: 99%
“…Some other recent studies (Lewko andGornowicz, 2011 andOhh, 2013) reported that soiled egg was higher on barn than in cages. The result is also partially supported by Belyavin (1988), who reported that the incidence of dirty and soiled eggs were higher on floor than in cages.…”
Section: Resultsmentioning
confidence: 83%